The influence of service marketing mix on customer loyalty towards telecommunication service provider in Malaysia - Nor Mazlan, Nor Amni Najwa (2021)
This study aims to determine the relationship between the service marketing mix and customer loyalty towards Malaysian telecommunications service providers. In this study, the service marketing mix's dimensions are represented by product, price, place, promotion, people, process, and physical evidence. Respondents of this study are UUM students who are undergraduate and postgraduate. A total of 395 questionnaire outcomes has been analyzed by using SPSS software version 26. Descriptive analysis, reliability analysis, Person's correlation analysis, and multiple regression analysis have been used to answer the research question and achieve the research objective in this study. This study shows that to achieve customer loyalty, the dimension of the service marketing mix, product, price, place, promotion, people, process, and physical evidence, caused an effect against that relationship. The study found a significant positive relationship between the dimensions of service marketing mix toward customer loyalty through the correlation test. Meanwhile, according to the multiple regression test, the result shows that the product, price, place, and physical evidence dimension became the significant factors influencing customer loyalty. Therefore, the telecommunications service providers should strengthen their service marketing mix through these elements. Through multiple regression tests also were resulted in the promotion, people, and process dimensions do not have a significant relationship towards customer loyalty. This shows that the telecommunications service providers could cut costs by not emphasize their service marketing mix by promotion, people, and process dimension because these dimensions were not suitable for a telecommunications service provider. However, the telecommunications service providers would innovatively be using the dimensions for influencing customer loyalty. Telecommunications service providers can use this study to improve their service marketing mix to influence customer loyalty in the future.